Antibiotic use from formal and informal healthcare providers in the Democratic Republic of Congo: a population-based study in two health zones. (September 2022) - Ingelbeen, Brecht; Phanzu, Delphin M.; Phoba, Marie-France; Budiongo, Mi Y.N.; Berhe, Neamin M.; Kamba, Frédéric K.; Kalonji, Lisette; Mbangi, Bijou; Hardy, Liselotte; Tack, Bieke; Im, Justin; Heyerdahl, Leonardo W.; et al.
Abstract: Objective: In the Democratic Republic of Congo and other low-resource countries, community-acquired pathogens are increasingly resistant to most locally available antibiotics. To guide efforts to optimize antibiotic use to limit antibiotic resistance, we quantified healthcare provider–specific and community-wide antibiotic use. Methods: From household surveys, we estimated monthly healthcare visit rates by provider. From healthcare visit exit surveys, we estimated prevalence, defined daily doses, and access/watch/reserve distribution of antibiotic use by provider. Combining both, we estimated community-wide antibiotic use rates. Results: Of 88.7 (95% CI 81.9–95.4) healthcare visits per 1000 person-months (n = 31221), visits to private clinics (31.0, 95% CI 30.0–32.0) and primary health centres (25.5, 95% CI 24.6–26.4) were most frequent. Antibiotics were used during 64.3% (95% CI 55.2–73.5%, 162/224) of visits to private clinics, 51.1% (95% CI 45.1–57.2%, 245/469) to health centres, and 48.8% (95% CI 44.4–53.2%, 344/454) to medicine stores. Antibiotic defined daily doses per 1000 inhabitants per day varied between 1.75 (95% CI 1.02–2.39) in rural Kimpese and 10.2 (95% CI 6.00–15.4) in (peri) urban Kisantu, mostly explained by differences in healthcare utilisation (respectively 27.8 versus 105 visits per 1000 person-months), in particular of private clinics (1.23 versus 38.6 visits) where antibiotic use is more frequent. The fraction of Watch antibiotics was 30.3% (95% CI 24.6–35.9%) in private clinics, 25.6% (95% CI 20.2–31.1%) in medicine stores, and 25.1% (95% CI 19.0–31.2%) in health centres. Treatment durations <3 days were more frequent at private clinics (5.3%, 9/169) and medicine stores (4.1%, 14/338) than at primary health centres (1.8%, 5/277). Discussion: Private healthcare providers, ubiquitous in peri-urban settings, contributed most to community-wide antibiotic use and more frequently dispensed Watch antibiotics and shortened antibiotic courses. Efforts to optimize antibiotic use should include private providers at community level.